Knowledge, attitude and beliefs of people in North India regarding blood donation - Dubey, Anju (Edizioni SIMTI - SIMTI Servizi Srl, 2014)
BACKGROUND: To develop targeted interventions in the field of donor recruitment, an understanding of existing knowledge, attitudes and beliefs regarding blood donation is required. Recruiters should be aware of variability in different demographic strata when implementing interventions. MATERIAL AND METHODS: A self-administered questionnaire along with a face-to-face interview was conducted in 400 each of voluntary donors, replacement donors and non-donors to assess their knowledge, attitude and beliefs regarding blood donation and their motivations for giving blood. Data were analysed using ANOVA and the c(2) test. RESULTS: The most common reason given by non-donors (40.75%) for not donating blood was “no one asked them to give blood”. Voluntary donors had a more pleasant blood donation experience compared to replacement donors and, therefore, more of them were willing to donate again (89.5%). The knowledge scores of non-donors were lower than those of donors and, among the latter, voluntary donors had better scores compared to replacement donors. Expectedly, the frequency of false beliefs was highest among non-donors (22.75%), with the most prevalent misbelief being that blood donation is associated with infertility. Television was found to be the most effective medium of communication for raising awareness about blood donation. CONCLUSION: It is recommended that extensive blood donation campaigning should be initiated, targeting the campaigns to eliminate specific misbeliefs and reinforce motivational perceptions. Blood centres should implement strategies to improve donor retention and should aim to provide a pleasant donation experience, regardless of the donor type. The idea of voluntary blood donation needs to be intensively promoted.